Is Guillain–Barré Syndrome Associated With COVID-19 Infection? A Systemic Review of the Evidence - Abdullahi, Auwal; Candan, Sevim Acaroz; Soysal Tomruk, Melda; Elibol, Nuray; Dada, Olumide; Truijen, Steven; Saeys, Wim (Frontiers in Neurology, 2021)
Background There is emerging evidence that, Guillain Barre Syndrome (GBS) may be associated with Covid-19 infection. The aim of this review was to investigate the strength of the evidence. Method The review was registered in PROSPERO (CDR42020184822). Three electronic databases, MEDLINE, PubMED and Web of Science and three preprint servers, MedRvix, ChemRvix and BioRvix were searched from December 2019 to 24th September, 2020. Studies were included if they were on Covid-19 and of any design. Articles that are reviews or opinion were excluded. The selection process was carried out using Endnote and Rayyan softwares. The main outcomes in the study were study design, sample size, sex, age, overall GBS symptoms, other Covid-19 symptoms, comorbidity, timing between infection and the onset of neurological symptoms, CT, MRI and EMG results. Methodological quality of the studies was assessed using McMaster Critical Review Form. The collected data was analysed using qualitative synthesis. Findings Fifty one high quality studies (mostly) consisting of 83 patients were included in the study. All of the patients (except in a very few) in the included studies had confirmed diagnosis of Covid-19. Similarly, the diagnosis of GBS was based on standard clinical, electrophysiological and CSF criteria. Conclusion GBS may be associated with Covid-19 and therefore testing for Covid-19 is recommended in patients presenting with GBS during this pandemic.